Adjustment disorder in cancer patients after treatment: prevalence and acceptance of psychological treatment - Van Beek, F. E.; Wijnhoven, L. M. A.; Custers, J. A. E.; Holtmaat, K.; De Rooij, B. H.; Horevoorts, N. J. E.; Aukema, E. J.; Verheul, S.; Eerenstein, S. E. J.; Strobbe, L.; Van Oort, I. M.; Vergeer, M. R.; et al. (Supportive care in cancer, 2022)
Purpose To investigate the prevalence of adjustment disorder (AD) among cancer patients and the acceptance of psychological treatment, in relation to sociodemographic, clinical, and psychological factors. Methods Breast, prostate, and head and neck cancer patients of all stages and treatment modalities ( N = 200) participated in this observational study. Patients completed the Hospital Anxiety and Depression Scale, Checklist Individual Strength, Distress Thermometer and problem list. Patients with increased risk on AD based on these questionnaires were scheduled for a diagnostic interview. Patients diagnosed with AD were invited to participate in a randomized controlled trial on the cost-effectiveness of psychological treatment. Participation in this trial was used as a proxy of acceptance of psychological treatment. Logistic regression analyses were used to investigate associated factors. Results The overall prevalence of AD was estimated at 13.1%. Sensitivity analyses showed prevalence rates of AD of 11.5%, 15.0%, and 23.5%. Acceptance of psychological treatment was estimated at 65%. AD was associated both with being employed (OR = 3.3, CI = 1.3–8.4) and having a shorter time since diagnosis (OR = 0.3, CI = 0.1–0.8). Conclusion Taking sensitivity analysis into account, the prevalence of AD among cancer patients is estimated at 13 to 15%, and is related to being employed and having a shorter time since diagnosis. The majority of cancer patients with AD accept psychological treatment.